How to prepare the researcher for indigenous context: an integrative approach. (2018) - Bindlish, Puneet K.; Nandram, Sharda S.; Gupta, Rajen; Joshi, Ankur
Indigenous methodologies refer to ethnography, storytelling and approaches that invite people to understand the local context which is culturally embedded and at the same time part of a global whole. In response to this recommendation, the authors propose a research paradigm that requires a fundamental change in the current configurations and models for organising institutions. It follows the research intention of providing cognitive schemas for a phenomenon through which it can be experienced as having a coherent integrative existence. For such experiences the researcher is the most significant actor and so in the proposed design, researcher preparation is the most important element. This paper focuses on the preparation of the researcher required, including the need for and process of this preparation and the implications for organisational research.